(3RgQI GdBOGH hKeQ GdCdHGHs - (3ddbGVi HMQ Hf UdGM Hf Ndjag Hf Ydj GdYGQhfi GdeGdcjs; (3EHQGgje Hf Ydj Hf Jeje GdCfUGQj, CHh ESMGb GdMUQj,J (B453 (3g` s ((3CMeO Hf YHOGdYRjR Hf Cjef GdYGeQj s)
(3ChdgG (B:s
(3hhUa CHhGdbQjI aQS GeQCI GdMLGL Edi YHOGdedc Hf eQhGf? MSf GdbQ, CSjd GdMQ, jSHb GdWQa hjSJZQb GdhUa s
(3BNQgG (B:s
(3abGd GYR Gddg GdhRjQ dh de CcPH eSJRjOkG , hde CQLY eSJajOkG, hEfi hEjGg ceG bGdJ GeQCI GdYRjR (B((3GdCf MUMU GdMb, GfG QGhOJg Yf faSg , hGg def GdUGObjf(B) s
(3HChdgG Jedc UdGM GdOjf GdUaOi GdeJhai (B764 (3g` HNWg hGdfSNI eYGQVI heUMMIs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B50 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B8s
Keywords: (3GdCOHs